2017
DOI: 10.1002/14651858.cd011126.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional saline infusion sonography compared to two-dimensional saline infusion sonography for the diagnosis of focal intracavitary lesions

Abstract: Low-quality evidence suggests that 3D SIS may be very accurate in detecting intracavitary abnormalities. Meta-analysis revealed no statistically significant differences between 2D SIS and 3D SIS. Summary sensitivity and summary specificity are higher for 3D SIS, but margins of improvement are limited because 2D SIS is already very accurate. When the technology and appropriate expertise are available, 3D SIS offers an alternative to 2D SIS. Both 2D SIS and 3D SIS should be considered alternatives to diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Few studies have used 3D PD to assess endometrial and subendometrial vascularization during the evaluation of endometrial lesions . Cil et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have used 3D PD to assess endometrial and subendometrial vascularization during the evaluation of endometrial lesions . Cil et al .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used 3D PD to assess endometrial and subendometrial vascularization during the evaluation of endometrial lesions. 6,12 Cil et al 6 reported that a single-vessel pattern was characteristic of endometrial polyps, whereas a rim-like vessel pattern was typical of a submucosal fibroid. However, those indicators were subjective.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were some limitations of the instrument when used with patients whose symptoms were caused by endometrial polyp or submucous leiomyoma. Nowadays, there are minimally invasive alternative methods used to detect endometrial polyp or submucous leiomyoma, such as three-dimensional saline infusion sonography (3D SIS) (Nieuwenhuis et al, 2017) and office hysteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 2D and 3D-SIS are useful in the diagnosis of diseases closely related to infertility, in particular myomas, endometrial polyps and Asherman's syndrome [14,15]. It allows the preoperative evaluation of benign intracavitary lesions [16]. Sonohysterography also plays an important role in secondary fertility investigation due to cesarian scar pregnancy.…”
Section: Sonohysterographymentioning
confidence: 99%